Gene-environment Interaction Models to Unmask Susceptibility Mechanisms in Parkinson's Disease - Chou, Vivian P. (MyJove Corporation, 2014)
Lipoxygenase (LOX) activity has been implicated in neurodegenerative disorders such as Alzheimer's disease, but its effects in Parkinson's disease (PD) pathogenesis are less understood. Gene-environment interaction models have utility in unmasking the impact of specific cellular pathways in toxicity that may not be observed using a solely genetic or toxicant disease model alone. To evaluate if distinct LOX isozymes selectively contribute to PD-related neurodegeneration, transgenic (i.e. 5-LOX and 12/15-LOX deficient) mice can be challenged with a toxin that mimics cell injury and death in the disorder. Here we describe the use of a neurotoxin, 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP), which produces a nigrostriatal lesion to elucidate the distinct contributions of LOX isozymes to neurodegeneration related to PD. The use of MPTP in mouse, and nonhuman primate, is well-established to recapitulate the nigrostriatal damage in PD. The extent of MPTP-induced lesioning is measured by HPLC analysis of dopamine and its metabolites and semi-quantitative Western blot analysis of striatum for tyrosine hydroxylase (TH), the rate-limiting enzyme for the synthesis of dopamine. To assess inflammatory markers, which may demonstrate LOX isozyme-selective sensitivity, glial fibrillary acidic protein (GFAP) and Iba-1 immunohistochemistry are performed on brain sections containing substantia nigra, and GFAP Western blot analysis is performed on striatal homogenates. This experimental approach can provide novel insights into gene-environment interactions underlying nigrostriatal degeneration and PD.